Pengaruh Tegangan Listrik Dan Waktu Pelapisan Hidroksiapatit Pada Logam 316L Dengan Metode Elektroforesis Deposisi (EPD) - Mayang Sari; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Stainless steel 316L is a metal which used to bone plate, this metal has low biocompatibility in a human body. The stainless steel 316L need to be coated by HA for increased their biocompatibility. The purpose of this research is to learn the effect of applied voltage and deposition time, then characterize HA coated 316L stainless steel. Stainless steel 316L put into alcohol and water solution for 1 hour. The HA powder was deposited by electrophoretic deposition (EPD) using carbon as anode and stainless steel 316L as cathode. It was observed from SEM analysis that HA deposited on stainless steel increased with higher voltage, thickness of HA layer on stainless steel was 30 μm, 45 μm and 55 μm for deposition 17 minutes and applied voltage 40, 60 and 80 volt. Thickness of HA layer on substrate increased, as the time deposition increased with result 30 μm dan 55 μm at deposition 80 volt and deposition time 2 and 17 minutes. HA coatings at applied voltage 80 volt and deposition time 17 minutes was obtained suitable for bone plate.Keywords : Coating, Electrophoretic Deposition, Hydroxyapatite, Stainless Steel 316L